Effects and mechanisms of digital economy development on corporate carbon emission intensity: empirical evidence from cross-country data - Da Yang; Zhao Yang; Haoze Wu (Digital Economy and Sustainable Development)
Abstract This study analyzes the effects and mechanisms of the digital economy on corporate carbon emission intensity through theoretical and empirical analysis. It explores the potential of the digital economy as a driving force for reducing corporate carbon emission intensity. It has been found that a country's digital economic development can reduce corporate carbon emission intensity by influencing the country's innovation level, energy structure, and total corporate factor productivity. Further analysis reveals that increased participation in global value chains and rising status will strengthen the carbon emission reduction effect of the digital economy; the carbon emission reduction effect of the digital economy is more evident in countries with weaker environmental regulation intensity.